GUGURNYA PERJANJIAN JUAL BELI AKIBAT KELALAIAN SALAH SATU PIHAK - Soekarno Soekarno (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTAgreement in general, the sale and purchase agreement is one source of the birth of an agreement between the parties that bind them as befits the binding capacity of the law (article 1338 paragraph 1 of the Civil Code). Therefore, all rights and obligations arising from the agreement must be fulfilled by both the seller and the buyer. It's just that sometimes in practice one of the parties in a sale and purchase agreement does not fulfill the achievement that has been promised so that according to the law he is deemed to have deviated from the agreement which will result in a risk that results in doubts from the other party. That is why the law stipulates various sanctions that can be imposed on parties who have defaulted. However, sometimes problems arise or difficulties in determining when actually one of the parties can be seen as the default. This difficulty will be felt if the agreement is not explicitly stipulated when the parties must fulfill the promised performance. Based on the aforementioned background, the writer is interested in expressing the cancellation of the sale agreement due to the negligence of one of the parties, then the writer formulates the problem as follows: 1). What are the conditions for the termination of the sale agreement due to the negligence of one of the parties? 2) What is the legal risk from the termination of the sale and purchase agreement due to negligence of one of the parties according to the Civil Code? It can be concluded as follows: 1). That the sale and purchase agreement has been deemed to have taken place and is binding on the parties from the moment the agreement was reached and hence the rights and obligations arising from them for agreements in this form constitute a consensual and obligatory agreement. That an agreement can be seen as binding, if it fulfills the legal requirements of an agreement, namely subjective and objective conditions, then the sale and purchase agreement is null and void, meaning that it is considered to never exist. 2). What if one of the parties does not fulfill or deviate from the agreement or the sale and purchase agreement that is entered into, then legally it is deemed to have been negligent or he is treason (default) then it will be subject to these sanctions. Whereas sometimes in practice a sale and purchase agreement cannot be fulfilled by the debtor due to an event of the wrongdoing of one party, this condition is known as risk, according to the provisions of article 1460 of the Civil Code. If a risk arises, the risk is borne by the buyer even though the seller has not yet surrendered the goods. Keywords: Agreement, Buy and Sell, Negligence